Simulating multicomponent multiphase electrohydrodynamic flows using a hybrid pseudopotential lattice Boltzmann and finite difference model - Jiachen Zhao; Shaofei Zheng; Hao Zhou; Zhongzheng Wang; Emilie Sauret (Physical Review Research)
Electrohydrodynamics (EHD) are widely utilized to manipulate fluid behaviors in practical applications, such as EHD high-resolution printing and EHD nebulization for producing monodispersed small droplets. In these applications, multicomponent multiphase (MCMP) phenomena with large density contrasts are usually involved. However, previous studies either focused on modeling single-phase multicomponent EHD problems where the densities of different components are the same or multiphase single-component EHD flows with large density contrasts where only one fluid component is considered. Therefore, in this work, a hybrid numerical framework combining MCMP pseudopotential LBM and FDM is implemented and applied to simulate EHD flows, which is capable of simulating MCMP EHD flows with large density ratios and offers tunable surface tension that is independent of viscosity and density ratios. The numerical model is comprehensively validated through benchmarks, including the thermodynamic consistency test, Young-Laplace droplet test, contact angle test, and droplet deformation under an electric field. The results demonstrate the capability of the present model for accurately simulating EHD MCMP flows with high-density ratios, good thermodynamic consistency, low spurious velocity, adjustable surface tension, and wettability. Lastly, the developed model is applied to investigate the effects of fluid electrical properties and electric field strength on the deformation and wettability of a sessile droplet under an external electric field.